Analisis Penerapan Jurnalisme Data Pada Pemberitaan RUU PKS Di Media Online Tirto.id - Danisa Novita Roka; Manalullaili, Manalullaili; Muslimin, Muslimin (Social Science and Contemporary Issues Journal, 2024)
International media has used data journalism since 2010 to prevent hoaxes. The media in Indonesia are also starting to use it now. Tirto.id is one of the leading media in Indonesia that applies data journalism. This research explores how Tirto.id utilizes data journalism in reporting on the RUU PKS, which has long been a matter of public debate. After carrying out the analysis in accordance with Teun A. Van Dijk's critical discourse analysis, observation, documentation and interview methods will be used. After the analysis is complete and the author reaches a conclusion, it will be presented in a qualitative descriptive manner. The author found that Tirto.id used data journalism in reporting on the RUU PKS by contacting sources to obtain data. Next, the verification team re-checks the data collected from the source to ensure the data quality remains good and prevent errors in delivery. After that, the data is evaluated and presented to the reader.